Design Process Optimization of Lower Arm Assembly Suspension - Azfar Zulkipli, Muhammad; Azam Abdullah, Shahrul; Sani Buang, Muhamad (International Journal of Engineering and Technology, 2018)
Metal stamping process is a process that converts blank sheet metal into complex shapes of component and parts with high dimensional accuracy at very short cycle time. Sheet metal stamping process involves upper and lower die. The upper part, or ‘ram’, uses gravity to fall upon the lower part, or ‘base’, of the press. A press operator loads a sheet metal blank into the press machine while the press is in the open position. Today, most factories require the press operator to ensure everything and everybody is clear of the press. Once safety has been considered, the operator simply presses a button and the ram falls upon the base. At the final process, the product will form into parts needed. Lower arm parts were identified to study the defect that contributes to the problem in the line production. In order to achieve the required shape at the final process, the best lower design and optimal condition of the stamping process needs to be achieved. This can be done experimentally by manipulating the operating conditions, machine set-up and tooling modifications. Therefore, this study focuses on optimization of the process parameter and introduction of a new lower arm design.